2014
DOI: 10.1002/stc.1713
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo local flexibility method for damage detection in hyperstatic beams

Abstract: Summary Vibration‐based damage detection methods make use of structural features extracted from vibration signals to perform damage diagnosis. The local flexibility method, which can determine local stiffness variations of beam structures by using measured modal parameters, is one of the more promising vibration‐based approaches. The local flexibility method is founded on ‘local’ virtual forces that cause nonzero stresses within a local part of the structure. In this study, this basic rule has been broken. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several advantages and limitations of these methods were also pointed out. Many studies confirm that mode shapes and corresponding mode shape curvatures are highly sensitive to damage and can be used for detection and quantification of the damage. Maia et al in performed extensive numerical simulations on a beam structure to compare damage identification sensitivity within different methods, based on the changes of mode shape, mode shape slope, mode shape curvature and mode shape curvature square, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several advantages and limitations of these methods were also pointed out. Many studies confirm that mode shapes and corresponding mode shape curvatures are highly sensitive to damage and can be used for detection and quantification of the damage. Maia et al in performed extensive numerical simulations on a beam structure to compare damage identification sensitivity within different methods, based on the changes of mode shape, mode shape slope, mode shape curvature and mode shape curvature square, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that sensitivity of changes in vibration characteristics was proportional to stiffness of a beam support; however, as damage severity increased, the respective change of nonlinearity did not follow the monotonic trend; therefore, it cannot be used for damage detection. Hsu et al suggested a local flexibility method built on a pseudo‐local virtual force action on the structure to identify local changes in stiffness in hyperstatic beams. Damage detection studies employed variation of a number of mode shapes.…”
Section: Introductionmentioning
confidence: 99%